Optimal Oil Pipeline Route Selection using GIS:Community Participation in Weight derivation and Disaster Mitigation - Matori, A.N (2012)
This paper uses the Geographical Information Systems (GIS) technique to generate an optimal oil pipeline route in Malaysia’s oil rich Baram Field. The project aims to ensure the generated route has the highest utility to the public, in addition to minimizing harmful impacts to people and the natural environment. Inputs from pipeline host communities where the pipelines will pass were seriously considered when determining the relative preferences of the various factors affecting the route (Weightings). This approach significantly increases the reliability and acceptability of the generated route. ESRI’s ArcGIS spatial analyst tool was deployed for data analysis and interpretation. Consequently, a more systematic, effective, and reliable pipeline routing process was developed.